Comparison of guidelines for the management of rectal cancer. Issue 6 (27th July 2018) - Luzietti, E.; Pellino, G.; Nikolaou, S.; Qiu, S.; Mills, S.; Warren, O.; Tekkis, P.; Kontovounisios, C.
Abstract : A comparison between NCCN, ESMO and JSCCR Guidelines is presented, concerning the treatment of rectal cancer, with an analysis and discussion of their discrepancies. Differences indicate areas for research